Letters IHS mounted on the pediment - Mumbai Archive Project Team (Jio Institute, 2024)
The letters IHS, encircled by a crown of thorns, are mounted on the pediment of the north projection. IHS represents a Christogram, a combination of letters forming an abbreviation for the name of Jesus Christ. Derived from the first three letters of the Greek name of Jesus (Ἰησοῦς), IHS consists of iota (Ι), eta (Η), and sigma (Σ).